ANTIOXIDANT ACTIVITY, SKIN IRRITAION POTENTIAL AND CHEMICAL COMPOSITION OF CLOVE LEAF OIL FROM WEST JAVA INDONESIA - Dwinna Rahmi; Retno Yunilawati; Ira Setiawati; Irwinanita Irwinanita; Bumiarto Nugroho Jati; Arief Riyanto; Yemirta Yemirta; Novi Nur Aidha (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2021)
ANTIOXIDANT ACTIVITY, SKIN IRRITATON POTENTIAL, AND CHEMICAL COMPOSITION OF CLOVE LEAF OIL FROM WEST JAVA INDONESIA. Essential oils with specific chemical compositions have the potential as a source of antioxidants in cosmetics, however, in general, essential oils are not safe because of the potential for skin irritation. This study aims is to perform fractionation to obtain clove oil with a chemical composition that is safe on the skin and does not reduce its antioxidant activity. Fractionation was performed at a temperature of 100 – 285 oC. Chemical composition was determined by Mass Chromatography Spectrometry (GC-MS), antioxidant activity by DPPH method, and irritation potential by in-vivo patch test. The results showed chemical components of clove oil were eugenol, copaene, beta caryophyllene, iso-eugenol, alpha caryophyllene, cadinene, caryophyllene oxide, caryophylla and beta caryophylla. Fractions with chemical compositions of eugenol and beta caryophyllene as the main components and copaene, iso-eugenol, alpha caryophyllene, cadinene as secondary components have very light erythema and no potential irritation to the skin. The fraction produced from the fractionation of crude clove oil at a temperature of 235 – 260 oC has the highest antioxidant activity of 10.17 mg/L.